Perbandingan Kinerja Keuangan Perusahaan Farmasi Milik BUMN dan Swasta di BEI Periode 2016-2018 - Lia Candrayani; Ziana Fitri; Kharis Fadlullah Hana (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
The purpose of this study was to determine the comparison of the financial performance of state-owned pharmaceutical companies with private-owned pharmaceutical companies and find out what factors affect differences in company performance based on analysis of profitability, market value rations and EVA. This study using a quantitative approach using a comparative descriptive method that took a sample of 4 pharmaceutical companies listed on the Stock Excahange. The data analysis technique uses a different independent sample T-test by comparing financial data from state-owned and private pharmaceutical companies in the 2016-2018 period. The results of the study show that return on equity (ROE) analysis of state-owned pharmaceutical companies is not safe because there are significant differences in the precentage above 15% and private pharmaceutical above 15%. The earning per share (EPS) analysis results of state-owned companies reached 0,35 and private pharmaceutical companies reached 50,71. As well as economic value added (EVA) analysis produces data there are differences in financial performace where the state-owned pharmaceutical companies have increased and privat pharmaceutical companies have decreased.